2021
DOI: 10.1016/j.envres.2020.110416
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the scientific production of the effect of COVID-19 on the environment: A bibliometric study

Abstract: The fight against COVID-19 since January 2020 has become the top priority of more than 200 countries. In order to offer solutions to eradicate this global pandemic, the scientific community has published hundreds of articles covering a wide range of areas of knowledge. With the aim of synthesizing these publications, academics are resorting to bibliometric analyses from the perspectives of the disciplines such as biology, medicine, socioeconomics and tourism. Yet no bibliometric analysis has explored the diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 83 publications
3
57
0
3
Order By: Relevance
“…The reduction in gas consumption and sharp reduction in international and domestic air traffic have also an important role in the reduction of the SO 2 levels around the world (Biswas et al 2020 ; Filonchyk and Peterson 2020 ; Pei et al 2021 ). Regarding O 3 , as a secondary pollutant, due to the NOx-sensitive regime, the observed reduction in NOx emissions would cause an increase in O 3 levels under a potential VOC-sensitive regime (Tables 3 – 4 and Figure 4 ) (Broomandi et al 2020 ; Casado-Aranda et al 2021 ; Kaskaoutis et al 2021 ; Kerimray et al 2020 ; Kumari and Toshniwal 2020 ; Lian et al 2020 ; Lokhandwala and Gautam 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in gas consumption and sharp reduction in international and domestic air traffic have also an important role in the reduction of the SO 2 levels around the world (Biswas et al 2020 ; Filonchyk and Peterson 2020 ; Pei et al 2021 ). Regarding O 3 , as a secondary pollutant, due to the NOx-sensitive regime, the observed reduction in NOx emissions would cause an increase in O 3 levels under a potential VOC-sensitive regime (Tables 3 – 4 and Figure 4 ) (Broomandi et al 2020 ; Casado-Aranda et al 2021 ; Kaskaoutis et al 2021 ; Kerimray et al 2020 ; Kumari and Toshniwal 2020 ; Lian et al 2020 ; Lokhandwala and Gautam 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…There are also some bibliometrics analyses that focus on some specific countries or regions (Gallegos et al, 2020;Raju & Patil, 2020) or publication sources (Oh & Kim, 2020). Beyond that, most of the bibliometrics analyses focus on some specific topics or fields, including COVID-19 and environment (Casado-Aranda et al, 2021;, mental health and COVID-19 (Maalouf et al, 2021), COVID-19 and machine learning (Chiroma et al, 2020;De Felice & Polimeni, 2020), COVID-19 and business and management (Rodrigues et al, 2020;Verma & Gustafsson, 2020), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al ( 2021 ) greatly emphasized the need to promote nanomaterial in utilizing pneumonia treatment to address the COVID-19 pandemic efficiently. Casado-Aranda et al ( 2021 ) found that scientific publications on writing COVID-19 pandemic are flared with the mixing of strategies and policies that need to be confined to strategic thinking and operational procedures the meaningful and smart inferences. The more traces found from the recent literature that confirmed the viability of innovation and green production process to improve healthcare sustainability agenda, which is likely to reduce coronavirus cases (see Mohideen et al 2021 ; Arribas-Ibar et al 2021 ; Ranjbari et al 2021 ; Dean et al 2021 ; Su and Urban 2021 ; Wang et al 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%